Kepuasan Pasien Terhadap Pelayanan Di Apotek Y Kota Bukittinggi - Nino Lady Ladika (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2023)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the patient's quality of life. Pharmacy is a certain place, where pharmaceutical work is carried out and distribution of health supplies to the community. The purpose of this study was to measure consumer satisfaction with the dimensions of reliability, responsiveness, assurance, empathy, and appearance of pharmaceutical services at the Y pharmacy in Bukittinggi. This type of research is descriptive, namely by using a questionnaire sheet as a research instrument and then calculating the average percentage of consumer satisfaction and classifying it. Based on the results of research conducted on 100 respondents, it can be concluded that the level of satisfaction with the reliability dimension is 83.70%, the responsiveness dimension is 80.43%, the guarantee dimension is 77.75%, the empathy dimension is 78.41% and the dimensions of tangible facilities are 77.80%. So that the average level of consumer satisfaction with pharmaceutical services at the Y pharmacy in Bukittinggi as a whole is 79.618% with the classification being Satisfied.